Dynamicity of language teacher motivation in online EFL classes. (December 2022) - Sak, Mehmet
Abstract: Despite the growing focus on the dynamic nature of second/foreign language (L2) teacher motivation in recent years, the existing work has primarily explored fluctuations in motivational trajectories over macro timescales covering months and years. Micro-scale changes of motivation at the lesson level and the factors underlying such changes have received little attention, particularly in the context of online instruction. The present study aims to close this gap by investigating dynamic changes in teacher motivation in the course of regularly-scheduled online English-as-a-foreign-language (EFL) classes in Turkey, as experienced by two EFL teachers at the tertiary level. Changes in motivation levels and the reasons for these changes were tracked in eight 45-min. classes over two weeks. Data were collected via self-ratings of motivational intensity at 5-min. intervals, journal entries, interviews, and lesson plans. The analysis showed considerable variation in the motivation levels within the participating teachers, with the fluctuations resulting from a complex array of learner-related, course-related, and individual factors. Overall, the findings provide further insights into the situated complexity of L2 teacher motivation and suggest that L2 teacher motivation to teach online is characterized by temporal, individual, and contextual variation, being open to influences and displaying nonlinear development over timescales.